Improving Students' Pre-Reading Skills Through Playing Picture and Word Cards at Nurul Hudha Serut Kindergarten (Universitas Sarjanawiyata Tamansiswa, 2024)
Pre-reading skills are essential foundational abilities that young children must acquire before entering the formal reading stage. However, many students struggle to recognize letters and words due to a lack of engaging and developmentally appropriate learning methods. This study aims to improve the pre-reading skills of Group B kindergarten students through the use of picture cards and word cards in a play-based activity. This research employed a descriptive qualitative approach. A total of 25 students actively participated in the study. The instruments used to collect data included interviews, observation, and documentation. The procedures consisted of planning, implementing actions, observing, and reflecting. Data were analyzed using triangulation techniques. The results showed an improvement in the pre-reading abilities of Group B students at TK Nurul Hudha, Serut, Gedangsari, Gunungkidul. This improvement demonstrates that the use of picture and word cards is effective in enhancing children's pre-reading skills. Therefore, this study concludes that a play-based approach using picture and word cards can serve as an innovative solution for early literacy instruction in kindergarten. This research contributes to enriching joyful and meaningful learning methods for early childhood education..